Multilateral development bank credit rating methodology: Overcoming the challenges in assessing relative credit risk in highly rated institutions based on public data - David Chen; Philippe Muller; Hawa Wagué (Bank of Canada, 2017)
The investment of foreign exchange reserves or other asset portfolios requires an assessment of the credit quality of counterparties. Traditionally, foreign exchange reserve managers and other investors have relied on credit rating agencies (CRAs) as the main source for credit assessments. The Financial Stability Board issued a set of principles in support of financial stability to reduce reliance on CRA ratings in standards, laws and regulations. To support efforts to end mechanistic reliance on CRA ratings and instead establish stronger internal credit assessment practices, this paper provides a detailed technical description of a methodology developed to assign an internal credit rating to multilateral development banks (MDBs), using only publicly available data. The methodology relies on fundamental credit analysis that produces a forward-looking assessment of the investment entity's capacity and willingness to pay its financial obligations, resulting in an opinion on the relative credit standing or likelihood of default. This methodology proposes four key innovations: (i) a simple way of estimating the capital adequacy ratio, (ii) new metrics to evaluate the liquidity and funding profile of an MDB, (iii) a straightforward approach to evaluating the exceptional support from shareholders, and (iv) a new criterion related to corporate governance, which provides a high level of objectivity in assessing some of the qualitative indicators. The methodology is a key component of the joint Bank of Canada and Department of Finance Canada initiative to develop internal credit assessment capabilities and is currently used to assess eligibility and inform investment decisions in the management of Canada's foreign exchange reserves.
Keywords: G24; G28; G32; F31; 330; Credit risk management; Foreign reserves management